PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR KANJI - Linda Sri Feni; Nana Rahayu; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Online learning is an educational innovation that involves elements of information technology in learning with a set of teaching methods where there are teaching activities that are carried out separately from learning activities. Japanese uses several letters in its writing, one of them is kanji. Kanji are letters that consist of elements of from, sound and meaning. From this it can be understood that kanji is an important aspect and effects the reading ability of Japanese learners themselves. The purpose of this study was to determine the effect of online learning on the result of kanji learning by using a descriptive quatitative approach. Data collection in this study used a written test and a questionnaire conducted on 33 respondents. From the results of this study obtained a moderate correlation.Key Word: Kanji, Online Learning, The Effect